Comprehensive transcriptome profiling and functional analysis of the meagre (Argyrosomus regius) immune system. Issue 123 (April 2022) - Monteiro, M.; Perdiguero, P.; Couto, A.; Serra, C.R.; Pereiro, P.; Novoa, B.; Figueras, A.; Ribeiro, L.; Pousão-Ferreira, P.; Tafalla, C.; Oliva-Teles, A.; Enes, P.; et al.
Abstract: Meagre ( Argyrosomus regius ) belongs to the family Sciaenidae and is a promising candidate for Mediterranean aquaculture diversification. As a relatively recent species in aquaculture, the physiological consequences of the immune system activation in meagre are understudied. Spleen, as a primary lymphoid organ has an essential role in meagre immune and inflammatory responses. In this study, we have evaluated the in vivo effects of lipopolysaccharide (LPS) on the spleen transcriptome of meagre by RNA-seq analysis at 4 and 24 h after injection.